Andréa Anthony: capstone - Anthony, Andréa, artist and filmmaker (Colorado State University. Libraries, 2016)
The artist's statement: I tend to gravitate towards commercial art and comic-type illustration, complete with bold graphic elements and neon colors. More often than not, I draw and design intuitively; whatever happens to pique my interest that day will ultimately manifest into a drawing or composition prior to the editing process that follows. Lately I've found myself torn between the analog and digital spheres of image making. Perhaps it is best to remain nonconforming toward either, and instead continue to encourage the push and pull between both worlds; for example, an illustration colored in with markers, scanned, and integrated into a digital design, or printing and drawing over vector graphics by hand. I restlessly peruse the internet not only for other likeminded artists but also inspiration - just prior to writing this statement, I had fallen into a violent whirlwind of art-related social media posts and had to consciously rip myself away.
Land and cloud
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, images of works and videos.
Videos have no spoken word.
Keywords: electronic art